2018
DOI: 10.1016/s1470-2045(18)30447-9
|View full text |Cite|
|
Sign up to set email alerts
|

The burden of cancers and their variations across the states of India: the Global Burden of Disease Study 1990–2016

Abstract: SummaryBackgroundPrevious efforts to report estimates of cancer incidence and mortality in India and its different parts include the National Cancer Registry Programme Reports, Sample Registration System cause of death findings, Cancer Incidence in Five Continents Series, and GLOBOCAN. We present a comprehensive picture of the patterns and time trends of the burden of total cancer and specific cancer types in each state of India estimated as part of the Global Burden of Diseases, Injuries, and Risk Factors Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
236
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(239 citation statements)
references
References 41 publications
3
236
0
Order By: Relevance
“…As far as India is concerned, in females there is a greater incidence of breast cancer followed by genitourinary cancers. 4 Present study also elucidated similar results with breast cancer being most common, followed by ovarian and cervical carcinomas. In males, oral cavity carcinomas account for the highest burden, followed by lung cancer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As far as India is concerned, in females there is a greater incidence of breast cancer followed by genitourinary cancers. 4 Present study also elucidated similar results with breast cancer being most common, followed by ovarian and cervical carcinomas. In males, oral cavity carcinomas account for the highest burden, followed by lung cancer.…”
Section: Discussionsupporting
confidence: 86%
“…In males, oral cavity carcinomas account for the highest burden, followed by lung cancer. 4 Present study sample for male patients was too small to comment on this, but around 11% were found to have both oral and lung cancer each.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Lung cancer, the most prevalent type of cancer today [43], is highly prevalent in India. It is the most prevalent cancer among males, and the seventh most prevalent among females [44], which correlates well with the differential tobacco smoking prevalence among males and females [6]. The most recent demographic data indicate that the recorded decline in tobacco usage in India noted in the intervening 7 years between GATS-1 and GATS-2 is probably insufficient to strongly reduce the prevalence of disease associated with tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The recent report of the global burden of disease study shows that cervical cancer incidence declined from the first position in 1990 to the third position in 2016 among all cancers in India and the Globocan 2018 shows that still, cervical cancer is in the second position of the most common cancers among women in India. [56] Although there is a reduction, the incidence of cervical cancer in rural India is still high compared to other parts of India. [789] In addition, the differences in quality and accessibility of health services make a wide variation in cervical cancer survival in India.…”
Section: Introductionmentioning
confidence: 99%